High efficiencies of gene delivery and gene targeting in embryonic stem cells of the fish medaka as a lower vertebrate model - Yan, Yan (2011)
This study reports the high efficiencies of gene delivery and gene targeting (GT) in a medaka fish embryonic stem (ES) cell model. A baculoviral (BV) vector is demonstrated to significantly improve gene delivery in medaka ES (MES I) cells, Furthermore, the BV mediated host integration does not compromise genome stability and pluripotency of transduced cells. GT via homologous recombination (HR) can generate precise genetic alterations in vertebrate genomes and has long been limited in mouse ES cells. It remains unresolved whether GT can also be developed in lower vertebrates. By using p53 as a gene model, the correct HR events are revealed by PCR, Southern, FISH and sequencing analyses, and a 22.8% GT efficiency is obtained in MES I cells. The pluripotency of targeted ES cells are well retained. These results demonstrate that highly efficient GT can be reproducibly obtained in MES I cells, offering a lower vertebrate model organism for GT towards knock-out animal production.